A Comparative Study of Vitamin C Concentrations in Two Selected Wild Fruits in Itojo Sub-County Ntungamo District. - Akankwatsa, Marither (Kabale University, 2024)
The body does not store vitamin C, making it essential to include vitamin C-rich fruits in the daily diet for maintaining good health. In the rural areas of Itojo sub-county, Ntungamo District, access to commonly consumed vitamin C-rich fruits such as oranges, lemons, and mangoes is limited, as these fruits are typically available only in urban market centers where they are sold. Additionally, rural residents often lack the financial resources to purchase these fruits from markets and supermarkets. This research aimed to determine and compare the vitamin C concentrations in two selected wild fruits, Horn melon (Cucumis metuliferus) and Seed of heaven fruit (Aframomum spp), which grow in the wild in rural Itojo sub-county, Ntungamo District. The vitamin C concentrations in the two selected wild fruits were measured using redox titration, where vitamin extracts from the wild fruits were titrated against potassium iodate solution with a starch indicator. The average volume of potassium iodate solution at the endpoint was recorded and used to calculate the vitamin C concentrations in the fruit extracts. The study found that the vitamin C concentration in three varieties of Horn melon (X1, X2, and X3) was 7.02 mg/100g, 7.39 mg/100g, and 6.49 mg/100g respectively. In contrast, the three varieties of Seed of heaven fruit (Y1, Y2, and Y3) had vitamin C concentrations of 23.23 mg/100g, 21.65 mg/100g, and 24.82 mg/100g respectively. Consequently, the study concluded that the vitamin C concentration in Seed of heaven fruits is almost three times higher than that in Horn melon fruits.